Exploring sarcoidosis via nailfold capillaroscopy: A window into the disease’s microvascular landscape - Mondini, Lucrezia; Barbieri, Mariangela; Trotta, Liliana; Monteleone, Giorgio; Ruggero, Luca; De Nes, Anna; Torregiani, Chiara; Cifaldi, Rossella; Antonaglia, Caterina; Hughes, Michael; Salton, Francesco; Confalonieri, Marco; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Sarcoidosis is a systemic granulomatous inflammatory disease that can affect virtually any organ, with a predilection for the lungs. It may present vasculitic features involving small, medium, or large vessels. Microvascular alterations in sarcoidosis can be assessed using nailfold videocapillaroscopy (NVC), a tool widely applied in the diagnosis and monitoring of systemic sclerosis, among other conditions. The aim of our study was to detect microcirculatory changes in patients with sarcoidosis and investigate their potential correlation with organ involvement. Methods: We conducted a single-center, retrospective case-control study involving three groups: 51 patients diagnosed with sarcoidosis, 51 healthy volunteers serving as controls, and 51 patients with systemic sclerosis. The groups were similar in sex and age. All participants underwent nailfold videocapillaroscopy (NVC) to assess microvascular changes. Results: This study confirmed the presence of non-specific microcirculatory abnormalities in patients with sarcoidosis, particularly in terms of reduced capillary density, the presence of angiogenesis, and slowed capillary flow. Although these alterations do not currently appear to correlate with specific clinical aspects of the disease, (e.g. the presence of autoantibodies, laboratory parameters and variables of lung function). Conclusions: Our findings confirm the presence of non-specific microvascular abnormalities in sarcoidosis. However, the identification of these capillaroscopic alterations as specific to sarcoidosis requires further confirmation. Ongoing studies aim to explore the potential role of NVC as a diagnostic marker and to investigate its correlation with the clinical manifestations of sarcoidosis.